Pemerolehan Bahasa Indonesia Pada Anak Usia Dini : Studi Kasus di TK Siwi Kencana Kota Langsa - Siregar, Prima Nucifera; Sari, Maulida; Novita, Anggria (Peneliti.net, 2024)
Language development in children begins when the child is born until the child in 5 years old. At this age, children can acquire a large vocabulary. This is what children get from their parents or from people around their environment, with different social backgrounds, so children can use appropriate language. Based on this statement, this study aims to analyze the acquisition of Indonesian in early childhood at Siwi Kencana Kindergarten, Langsa Baro District, Langsa City in the categories of phonology, morphology, syntax and semantics. This study uses a qualitative descriptive method because research want to describe the results of research that occurs want to describe the results of research that occurs in every day life which are fact in the acquisition of Indonesian in early childhood. Meanwhile this data was obtained through observation. The data contained in this study are utterances in the form of words, phrases, clauses or sentences produced by early childhood. The data sources is early childhood and the research location is Siwi Kencana Kindergarten, Langsa Baro District, Langsa City. The results of this study indicate that there is a change in the phoneme /r/ to /l/ at the age of 5 years. Meanwhile, the there are some children who clearly pronounce vowels and consonants. At the age of 4-5 years, children are able to pronounce vowel letters such as /a/,/i/,/u/,/e/,/o/, and other consonant letters.